2021
DOI: 10.3390/v13101942
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial F-G Immunogens as Nipah and Respiratory Syncytial Virus Vaccine Candidates

Abstract: Nipah virus (NiV) and respiratory syncytial virus (RSV) possess two surface glycoproteins involved in cellular attachment and membrane fusion, both of which are potential targets for vaccines. The majority of vaccine development is focused on the attachment (G) protein of NiV, which is the immunodominant target. In contrast, the fusion (F) protein of RSV is the main target in vaccine development. Despite this, neutralising epitopes have been described in NiV F and RSV G, making them alternate targets for vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…G glycoprotein is considered an important antigen for NiV vaccine development. Many vaccines that use Nipah virus G protein or G protein + F protein as antigens are under development ( Guillaume et al, 2004 ; Prescott et al, 2015 ; Singh et al, 2019 ; Isaacs et al, 2021 ). The results showed that most neutralizing antibodies were induced by G protein ( Weingartl et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…G glycoprotein is considered an important antigen for NiV vaccine development. Many vaccines that use Nipah virus G protein or G protein + F protein as antigens are under development ( Guillaume et al, 2004 ; Prescott et al, 2015 ; Singh et al, 2019 ; Isaacs et al, 2021 ). The results showed that most neutralizing antibodies were induced by G protein ( Weingartl et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudovirus neutralisation assays were conducted using lentivirus-based pseudotypes as previously described ( 51 53 ). Briefly, HEK293T cells were transfected with p8.91 (encoding for HIV-1 gag-pol), CSFLW (lentivirus backbone expressing a firefly luciferase reporter gene) and viral glycoprotein (NiV F + G or LASV GPC) using PEI transfection reagent.…”
Section: Methodsmentioning
confidence: 99%
“…A similar approach to that undertaken with RSV was recently shown to stabilize the NiV and HeV F glycoproteins in the prefusion conformation 26 . In parallel, we have previously shown that prefusion NiV F can be stabilized by a novel molecular clamp trimerization domain in the absence of heterologous mutations 25 , 28 . Here, we use a similar approach to determine the structures of LayV and MojV F glycoproteins in the prefusion conformation via cryogenic electron microscopy (cryo-EM) and to characterize their glycosylation profiles with mass spectrometry glycoproteomics, in order to inform future vaccine design and therapy against these emerging viruses.…”
Section: Introductionmentioning
confidence: 91%
“…This outlines a rational basis for neutralizing antibody discovery and structure-based vaccine design against prefusion F. Indeed, several antibodies targeting the prefusion conformation of F have been isolated and shown to be neutralizing and protective 21 24 . Moreover, vaccine studies with prefusion-stabilized NiV F have been shown to elicit potent neutralizing responses 25 28 . While these studies yielded vital information into HNV vaccine design, it is unknown whether this immunity extends to other divergent HNVs such as MojV and LayV.…”
Section: Introductionmentioning
confidence: 99%